The Effect Of Decline Push Up And Bench Dip Exercise On Smash Outcomes In Puma Volley Club Volleyball Athletes - M, Benny Aprial.; Sari, Liliana Puspa; Hendrawan, Dicky; Sari, Dewi Maya; Giawa, Epenetus (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2023)
This study aims to determine the effect of decline push up and bench dip exercises on the arm muscle strength of Puma Volley Club Volleyball athletes, Serdang Bedagai. This research was conducted at Puma Volleyball Club Serdang Bedagai Volleyball. The population of this study was 8 people and the sample used in this study were male athletes, totaling 8 people who were taken by simple random. This research method is an experimental method with the research design Pretest – Posttest One Group with decline push up and bench dip exercises carried out for 6 weeks. The test instrument used is a test of the results of the arm muscle strength. The data analysis technique used was the Lilifors normality test and the hypothesis test, namely the t-test with a significant level of 0.05. The results obtained from the hypothesis test, namely the strength of the arm muscles, obtained tcount (5.63) > ttable (1.90). Based on the criteria for testing the hypothesis, then Ha is accepted and Ho is rejected so that it can be concluded that there is an effect of decline push up and bench dip exercises on the arm muscle strength of Puma Volley Club Volleyball Serdang Bedagai athletes.